PENINGKATAN HASIL BELAJAR SISWA PADA MATERI CERPEN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA MAGIC BOOK DI KELAS IV SDN 2 MEURAH DUA - Riskiana; Alfi Syahrin; Muhammad Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students' learning outcomes, teacher and student activities, and to determine the responses of fourth-grade students at SDN 2 Meurah Dua toward learning short stories through the implementation of the Problem Based Learning (PBL) model assisted by Magic Box media. The background of this study was the low student learning outcomes caused by monotonous teaching methods and the limited use of engaging learning media. This research employed Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 19 fourth-grade students. Data were collected through learning achievement tests, observation sheets of teacher and student activities, and interviews. The results showed a significant improvement in students' learning outcomes, with the classical learning mastery increasing from 63.15% (12 students) in Cycle I to 84.21% (16 students) in Cycle II. Teacher activity improved from an average score of 82.5% in Cycle I to 93.75% in Cycle II, which was categorized as